DETERMINANTS OF FOREIGN DIRECT INVESTMENT: A PANEL REGRESSION ANALYSIS OF INSTITUTIONAL, ECONOMIC, AND INFRASTRUCTURE FACTORS - Ashurov Ramazon Tura ugli; Yusupov Komaliddin Bakhtiyor ugli; Bakhodirov Jakhongir Bakhodir ugli; Omonova Navruzoy Ruzibek kizi (Web of Journals Publishing, 2025)
This study examines how institutional quality and macroeconomic fundamentals influence foreign direct investment inflows (FDI) as a share of GDP in 20 countries across Africa and Asia from 2016 to 2023. We employ an Ordinary Least Squares (OLS) panel regression on 160 country-year observations to assess the impact of corruption, political stability, corporate taxation, infrastructure, economic development, and inflation on FDI. Diagnostic tests (residual analysis, multicollinearity via VIF, normality, and autocorrelation checks) are conducted to validate OLS assumptions. The results indicate that better transport infrastructure and lower corporate tax rates are significantly associated with higher FDI/GDP, holding other factors constant. Political stability also shows a positive relationship with FDI, reinforcing the importance of a stable governance environment. In contrast, the corruption perception index and inflation rate exhibit no statistically significant effects in the multivariate setting, possibly due to multicollinearity or the sample’s regional characteristics. These findings align with much of the existing literature, though the insignificant corruption effect suggests that its influence may be indirect or captured by other variables. Policy implications include investing in infrastructure, maintaining competitive tax regimes, and strengthening political stability to attract FDI. The paper contributes to the understanding of FDI determinants in the post-2016 context, including the turbulent COVID-19 period, offering insights for policymakers in emerging economies.
Keywords: Foreign Direct Investment; Institutional Quality; Infrastructure; Corporate Tax Rate; Political Stability; Panel Data; OLS Regression